Techno-mathematical literacies in digital age: Which categories are importance for teachers? - Kartika, Hendra; Hastari, Ratri Candra (UNIVERSITAS NEGERI MALANG, 2022)
Nowadays, digital technologies development potentially have changed on teaching and learning activities and demands teachers’ competencies and literacy. In this study, narrative review is used to identify the types of Techno-mathematical Literacy (TmL) that the teachers need to acquire in this digital age. There are seven categories of TmL studied, namely: data literacy, ability to use computer software, communication skills, ability to analyze errors, ability to interpret numbers, creativity, and drawing skills. The results show that the seven categories are crucial for teachers to execute their role in this highly demanding era. These results also indicate that techno-mathematical literacy needs to be applied in the field of teacher education to adequately equip the students with the skills required in the workplace. The result also suggested that teachers need to be encouraged to develop their instructional design in the attempt to enhance students’ techno-mathematical literacy.